Alternative recreational and recreational activities in the subjective well-being of school children today(Original) (Revista científica Olimpia, 2020)
In the present investigation, it was proposed as an objective to design an alternative based on recreational and participatory activities, which favors the state of subjective well-being in the schoolchildren of the Abrahán Martínez Castañeda Primary School of the Jiguaní municipality. This objective was fulfilled in the course of the investigation through the introduction of theoretical methods such as: historical-logical, analysis-synthesis, inductive-deductive and functional structural systemic. Among the empirical ones: observation, measurement and pre-experiment, to analyze and compare the initial and final diagnosis. As the main technique, the Global Satisfaction Index for Fields (IGSA) was applied, calculated using the arithmetic mean of 8 indexes of areas of children's lives. The content of the alternative based on recreational and participatory activities is flexible and allows the participation of social actors in the community.
Keywords: subjective well-being; leisure activities; physical recreation